Evaluation of Microstructure and Hardness of AISI D2 Steel by Time Quenching in Comparison with Water and Oil Quenching (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Due to an account of its excellent hardness and wear behavior, AISI D2 is used widely in producing of blanking and cold-forming dies, Punches, Shafts, Studs, and Bolts. Increasing toughness at a fixed high level of hardness is growing requirement for this kind of applications. Improving microstructure characteristics, especially carbides distribution by specific heat treatment, is an appropriate way to meet such requirement. The effect of quenching media on microstructure and hardness of pre-heated and austentized (at 980oC) AISI-D2 tool steel has been studied, and hardness and carbides morphology have been investigated. Three different medias, water, oil and water/oil (time quenching) have been used, then all samples were followed by the same tempering 350oC/1 hour. It has been found that the optimal carbides distribution and optimum hardness have been resulted from a time quenching method.